PENYESUAIAN DIRI PESERTA DIDIK PINDAHAN DALAM BELAJAR DI MTs TI BATANG KABUNG PADANG - Mirawati, Hermina; Arief, Asmaiwaty; Yusnetti, Yusnetti (Bimbingan dan Konseling, 2013)
This study looks at the phenomenon was still a student experiencing difficulties in adapting and too awkward to adjust to school. This study aims to describing 1)  adjustment of transfer student participants learn with teachers 2)  adjustment of transfer students in learning with the teacher,  and 3) adjustment of transfer students in learning in the school environment. This research is a descriptive study of a state trying to describe what it is.  The population is moving MTs TI learners Batang Kabung Padang. Total population of 23 people  Samples were selected based on technique total sampling.  Sources of data in this study is primary data is data obtained from a transfer student questionnaires and secondary data is data that has been obtained from the administration of transfer students.  Data collection techniques in this study using a questionnaire. The results of the data in this study were processed using techniques percentage. The results revealed that 1)  the adjustment in the transfer of students studying with a friend on unfavorable criteria, 2) the adjustment of moving students in learning with the teacher on unfavorable criteria, and 3)  adjustment of transfer students to the school environment in unfavorable criteria.  Based on the results of these studies are expected to transfer students to be able to better adjust to the new school had their come. To the guidance and counseling teachers in order to help learners to make adjustments within the school .